ESEM observation and rheological analysis of rejuvenated SBS modified bitumen. (June 2021) - Lin, P.; Liu, X.; Apostolidis, P.; Erkens, S.; Zhang, Y.; Ren, S.
Abstract: Observing the microstructure of bituminous binders with an environmental scanning electron microscope (ESEM) can contribute significantly to reveal the underlying rejuvenation mechanism. In this study, three rejuvenators were selected to regenerate the aged SBS modified binders at five dosages, and their rheology was evaluated using a dynamic shear rheometer. ESEM was employed to examine the microstructure of binders as well, and a series of microstructure parameters were quantified with image analysis. The results demonstrated that the chemical composition changes correspond to the evolution of microstructure morphological and rheological properties. Moreover, the rheological and microstructure characteristics were analyzed with Principal Component Analysis (PCA) and regression analysis. Based on PCA results, the microstructure of rejuvenated binders has shown a good correlation with stiffness after combining various principal components. According to regression analysis, the distance between adjacent fibrils exhibited a significant correlation with Jnr3.2 and the complex modulus index. Overall, the results of this study strengthen the hypothesis that the ESEM microstructure is intimately correlated with chemical composition and rheological properties, rather than with irrelevant surface phenomena. Bitumen, polymer modified bitumen, rejuvenator, microstructure, rheology, environmental scanning electron microscopy. Graphical abstract: Unlabelled Image Highlights: The addition of rejuvenators contributes to the formation of fibril structure and increases the distance between fibrils. The influence of rejuvenator types/dosages on the fibril-structure can be demonstrated with ESEM. A process for extracting quantification parameters from the fibril-structure of bitumen is proposed. The fibril-structure parameters exhibited a significant correlation with rheological properties.